Influence of shape on particle size analysis - Ferreira, P. J. (1993)
The purpose of this paper is to study the influence of the shape of the particles on the response of the instruments used for their measurement. This was achieved by sizing three different particle shape materials with three different particle sizers. The differences in the size distribution data were used to calculate shape factors, defined as the ratio of two different equivalent diameters, The values of these shape factors were subsequently used in a “model shape” approach in order to cross-check the data